The Influence of Computer Self-Efficacy, Taxation Knowledge And Modernization of The Tax System On The Use of Tax E-Systems For MSMES During The Covid-19 Pandemic - Licke Bieattant; Ika Wahyuni; Aprilia Putri Andriani (Eduvest - Journal of Universal Studies, 2023)
The purpose of this study was to analyze the effect of computer self-efficacy, tax knowledge and modernization of the tax administration system on the use of the e-Taxation System in the utilization of the Covid 19 Pandemic Tax Incentive for UMKM Taxpayers in DKI Jakarta. This study uses quantitative research methods. Based on data analysis, it is known that the value of t_count > t_table, this proves that computer self-efficacy, Tax Knowledge and Modernization of the tax administration system have a positive effect on the use of the e-Taxation System in the utilization of Covid 19 Pandemic Tax Incentives for UMKM Taxpayers. This shows that computer self-efficacy, knowledge of taxation and modernization of the tax administration system have a positive influence in its implementation, where the implementation of a transparent and accountable tax administration system, mastery of comprehensive tax knowledge as well as everyone's expertise and curiosity about the E-Taxation System Application Program by the government in simplifying the implementation of tax obligations. With the improvement of the tax administration system, knowledge and ability of a person in mastering computers, the higher the curiosity of a person to use the e-Taxation System in the use of Tax Incentives for UMKM Taxpayers affected by the Covid 19 Pandemic.